The last flight ebook A novel. - Clark, Julie (2020)
THE INSTANT NEW YORK TIMES, USA TODAY BESTSELLER, & INTERNATIONAL BESTSELLER! Look for The Ghostwriter, the next novel from Julie Clark, coming in June 2025! "The Last Flight is thoroughly absorbing—not only because of its tantalizing plot and deft pacing, but also because of its unexpected poignancy and its satisfying, if bittersweet, resolution. The characters get under your skin."—The New York Times Book Review Two women. Two flights. One last chance to disappear. Claire Cook has a perfect life. Married to the scion of a political dynasty, with a Manhattan townhouse and a staff of ten, her surroundings are elegant, her days flawlessly choreographed, and her future auspicious. But behind closed doors, nothing is quite as it seems. That perfect husband has a temper that burns bright and he's not above using his staff to track Claire's every move. What he doesn't know is that Claire has worked for months on a plan to vanish. A plan that takes her to the airport, poised to run from it all. But a chance meeting in the airport bar brings her together with a woman whose circumstances seem equally dire. Together they make a last-minute decision. The two women switch tickets, with Claire taking Eva's flight to Oakland, and Eva traveling to Puerto Rico as Claire. They believe the swap will give each of them the head start they need to begin again somewhere far away. But when the flight to Puerto Rico crashes, Claire realizes it's no longer a head start but a new life. Cut off, out of options, with the news of her death about to explode in the media, Claire will assume Eva's identity, and along with it, the secrets Eva fought so hard to keep hidden. For fans of Lisa Jewell and Liv Constantine, The Last Flight is the story of two women—both alone, both scared—and one agonizing decision that will change the trajectory of both of their lives. Praise for The Last Flight: "The Last Flight is a wild ride: One part Strangers on a Train, one part Breaking Bad, with more twists than an amusement park roller coaster! Julie Clark is a devilishly inventive storyteller." — Janelle Brown, New York Times bestselling author of Watch Me Disappear and Pretty Things "The Last Flight is everything you want in a book: a gripping story of suspense; haunting, vulnerable characters; and a chilling and surprising ending that stays with you long after the last page." — Aimee Molloy, New York Times bestselling author of The Perfect Mother "The perfect combination of beautiful prose and high suspense, and an ending that I guarantee will catch you off guard." — Kimberly Belle, internationally bestselling author of Dear Wife and The Marriage Lie "The Last Flight sweeps you into a thrilling story of two desperate women who will do anything to escape their lives. Both poignant and addictive, you'll race through the pages to the novel's chilling end. A must read of the summer!" — Kaira Rouda, internationally bestselling author of Best Day Ever and The Favorite